Assembly of Gold Nanoparticles on Functionalized Si(100) Surfaces through Pseudorotaxane Formation. Issue 24 (18th April 2013) - Boccia, Alice; D'Orazi, Fabio; Carabelli, Elena; Bussolati, Rocco; Arduini, Arturo; Secchi, Andrea; Marrani, Andrea G.; Zanoni, Robertino
Abstract The assembly of gold nanoparticles (AuNPs) on a hydrogenated Si(100) surface, mediated by a series of hierarchical and reversible complexation processes, is reported. The proposed multi‐step sequence involves a redox‐active ditopic guest and suitable calix[n]arene‐based hosts, used as functional organic monolayers of the two inorganic components. Surface reactions and controlled release of AuNPs have been monitored by application of XPS, atomic force microscopy (AFM), field‐emission scanning electron microscopy (FESEM) and electrochemistry.